Peningkatan Mutu Sumber Daya Manusia melalui Pelatihan Budi Daya Rumput Laut dan Berbagai Makanan Olahannya, serta Pengelolaan Terumbu Karang Guna Peningkatan Potensi Daerah Menuju Kemandirian di Kec. Laonti Kab. Konawe Selatan - Ratna Diyah Palupi; Abdul Rahman; Nurdiana A (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2016)
This program was carried out in the Tambolosu and Rumbi-Rumbia villages which is a coastal village in district of South Konawe. As a coastal village communities would have been very different characteristics with the majority of the land village. It is a fact that the majority of people in these villages are working as fishermen, so they financial life is dependent on the fishery resources. Meanwhile the high potential of coastal resources are not comparable with the quality of human resources. The purposes of these service community are to enhance participation of target community to make a coastal and marine resources management, namely, coral reefs, sea grass, and fish. The second aim are for Halu Oleo students who joint in this program for make problem solving in the society with related with they  college material. There are four programs was done, namely seaweed cultivation by using long line methods, restoration of coral reefs through artificial reefs and coral transplants, and the last program is manufacture of processed food made from seaweed and fish (seaweed chips, fish meatballs, legs dragon, and cendol seaweed ice. The method used observation and experimentation, analysis techniques using qualitativede scriptive method. The Results of the community services by Halu oleo lecturer are the level of community participation is in the high level in both villages as the target society. Participation of the target society were also seen with the good cooperation with students for example for determining site selection and placement in the waters for artificial reef and coral transplantation. In addition both villages of  target by fisheries and marine sains faculty will be a “village built” to sustainability in order to achieve public welfare activities.